Анна Каренина: роман в 8 частях / Л. Н. Толстой - Толстой Лев Николаевич (Издательство ЛГУ, 1978)
Экземпляры: КХ (20111111) / Инвентарный номер: 688010 / Сис.шифр: Р1 / Авт.знак: Т 53 / ГРНТИ: 17 / ББК: 84(2=411.2)-4